Bilateral nipple-sparing mastectomy and breast reconstruction in BRCA1 mutation-positive simultaneous bilateral breast cancer: A case study. (April 2021) - Yoneyama, Kimiyasu; Nakagawa, Motohito; Hara, Asuka
Highlights: BRCA-positive breast cancer with bilateral subcutaneous mastectomy and breast reconstruction. The patient was able to be diagnosed preoperatively. Performing a preoperative BRCA test may change the surgical procedure. Increasing numbers of BRCS tests may change surgical treatment strategies. This is the first report in Japan. Abstract: Background: Mutation-positive patients who develop unilateral breast cancer require different treatments, such as prophylactic mastectomy of the contralateral breast, from those used for other breast cancer patients. If a mutation is found before surgery, it is necessary to consider a surgical procedure that includes reconstruction. For BRCA mutation-positive patients, a suitable treatment must be selected. In Japan, a test for BRCA mutation has been covered by health insurance since 2020, making it possible to preoperatively test patients who are suspected of being positive. We report a case of simultaneous bilateral breast cancer that was found to be BRCA mutation-positive preoperatively and underwent bilateral subcutaneous mastectomy and breast reconstruction. Case presentation: A 57-year-old woman was admitted to our hospital after a breast cancer screening revealed a mass in the left breast. She had a family history of breast cancer, including her sister, aunt, and cousin. She was suspected of being malignant with a mass on both sides of her breast on imaging. She underwent needle biopsy and was diagnosed as having bilateral invasive ductal carcinoma, for which she was placed on preoperative chemotherapy. Due to the strong family history of bilateral breast cancer, the patient was recommended to undergo a BRCA gene-mutation test and she consented. The result was positive for BRCA1 mutation. Although it was judged that bilateral breast-conserving surgery was sufficiently possible, bilateral subcutaneous mastectomy and breast reconstruction were performed based on BRCA mutation-positive status. Discussion: Performing a preoperative BRCA test may change the surgical procedure. BRCA tests are beneficial to patients, but the timing of the tests is important. Care must be taken not to force the patient. Conclusions: Knowing whether the patient is BRCA mutation-positive is extremely important for selecting surgical procedures and treatment methods. BRCA testing should be recommended for patients who are strongly suspected of being positive, but the decision should be the patient's. It is therefore necessary to provide accurate information and engage in a dialogue with the patient, but the medical staff should not pressure the patient to have the test.